A blockchain-based approach to smart cargo transportation using UHF RFID - Baygin, Mehmet; Yaman, Orhan; Baygin, Nursena; Karakose, Mehmet (Pergamon-Elsevier Science Ltd, 2022)
Today, the continuous growth of electronic commerce volume increases the importance of point-to-point shipment transportation. For this reason, it is extremely important that shipment management systems provide effective, efficient and fast service. A study of the literature shows that the improvements made in the field of transportation have been generally aimed at global logistics networks. In this study, unlike the existing literature, a blockchain-based solution is developed for local cargo networks. With this approach using Ultra High Radio Frequency (UHF-RFID), Internet of Things (IoT) sensors and blockchain-based smart contracts, a fast shipping management architecture that ensures security between the parties is provided. In this context, an automatic payment and approval mechanism is established between the parties using ethereum-based smart contracts. In addition, shipments equipped with RFID tags are automatically tracked and traceable using UHF-RFID antennas. The IoT data collected in the study are stored on a cloud-based server, which is a cost-effective solution. Smart contracts that enable communication between the parties are written in the Solidity language using the Ganache, Truffle and Metamask platforms. It was observed that the integration between the technologies is ensured and the communication between the parties works successfully in the test processes.
Keywords: Blockchain; Smart Contract; UHF-RFID; Smart Cargo Management; Smart Applications